TANTANGAN PELAYANAN PUBLIK DI IBU KOTA NEGARA (IKN) NUSANTARA - Haryo Setyoko; Suhud Alynudin; Agus Widiarto (LPPM STIA Banten, 2022)
The relocation of the National Capital City (IKN) of the Archipelago from DKI Jakarta to Kalimantan became the government's current focus is on the national recovery period caused by the pandemic Covid-19. Limited funds, less strategic location from a security perspective, as well forest fire disasters that often occur since Kalimantan is one of them the lungs of the world, including the natural wealth contained therein, become something what is important to note. One of them is by using a service approach based on the Development Program of the United Nations (UN), namely Tata Manage Good governance. The research method used is through the study literature, such as documents from official government institutions and sources other relevant. Referring to the newly passed regulation, the government has already loaded it public services in accordance with good governance. Process the transfer of the capital city needs to be escorted so that the previous evaluation is like the people who not yet involved not repeated.